2022
DOI: 10.1109/tse.2020.3023177
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Defective Lines Using a Model-Agnostic Technique

Abstract: Defect prediction models are proposed to help a team prioritize source code areas files that need Software Quality Assurance (SQA) based on the likelihood of having defects. However, developers may waste their unnecessary effort on the whole file while only a small fraction of its source code lines are defective. Indeed, we find that as little as 1%-3% of lines of a file are defective. Hence, in this work, we propose a novel framework (called LINE-DP) to identify defective lines using a model-agnostic techniqu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 75 publications
(33 citation statements)
references
References 89 publications
(163 reference statements)
0
27
0
Order By: Relevance
“…Yan et al [43] proposed a two-phase approach-i.e., the ML model trained on software metrics (e.g., #added lines) is first used to identify which commits are the most risky, then the N-gram model trained on textual features is finally used to localise the riskiest lines. On the other hand, a recent work by Wattanakriengkrai et al [42] pointed out that a machine learning approach outperforms the n-gram approach. However, their experiment focused solely on file-level defect prediction-not Just-In-Time defect prediction.…”
Section: Related Work and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yan et al [43] proposed a two-phase approach-i.e., the ML model trained on software metrics (e.g., #added lines) is first used to identify which commits are the most risky, then the N-gram model trained on textual features is finally used to localise the riskiest lines. On the other hand, a recent work by Wattanakriengkrai et al [42] pointed out that a machine learning approach outperforms the n-gram approach. However, their experiment focused solely on file-level defect prediction-not Just-In-Time defect prediction.…”
Section: Related Work and Research Questionsmentioning
confidence: 99%
“…In our studied projects, we found that the average size of the commit varies from 73 to 140 changed lines, but the average ratio of actual defective lines is as low as 51%-53%. Thus, developers still spend unnecessarily effort on locating actual defective lines of that commit [42]. To address bors.…”
Section: Related Work and Research Questionsmentioning
confidence: 99%
“…Besides of helping understand the behaviour of deep learning models, interpretability methods have also been used to directly improve the process of software engineering. For example, [43], [44] used LIME [45], a model-agnostic explainability method, to pinpoint the defective lines of code from defect detection models.…”
Section: I M O D E L I N S P E C T Io Nmentioning
confidence: 99%
“…Interpretable or explainable deep learning based Android malware analysis is also a future interesting topic [60,160]. Recently, researchers have focused on conducting empirical studies to highlight the need of explainable AI/ML models for software engineering [75] and developing novel approaches for explainable AI/ML models for software engineering [75,83,125,125,129,135,176]. Although existing studies have attempted to employ local explainable approaches to provide explanations based on the Android characteristic-based features for each unknown sample [179], there are still several issues requiring further exploration.…”
Section: Rq22: What Deep Learning Architectures Are Used?mentioning
confidence: 99%